DETERMINANTS OF INTEREST IN USING TRAVEL VLOGS ON YOUTUBE AS A REFERENCE FOR TRAVELING - Mamori, Dore Rhendy; Najib, Mukhamad; Maulana, Agus (Jurnal Aplikasi Manajemen, 2020)
This study aims to analyze the demographic characteristics, usage behavior, and things that have an impact on attracting viewers to watch and utilize travel vlogs on YouTube as a travel reference. respondents in this study 131 were selected based on criteria aged 18 years and over and had watched travel vlogs on youtube at least once in 3 months to find travel reference information. The analytical tool used in this study is the Structural Equation Model (SEM) using LISREL software. The results of this study are to find out things that affect interest in using travel vlogs on YouTube based on nine hypotheses. First, the popularity of the travel vlog variable does not affect the credibility of the perception variable. Variable perception of interest, attitude variables towards use have a significant effect. Second, the video characteristic variable influences the perception variable of credibility. Third, the video characteristic variable influences the perception of benefits. Fourth, the credibility perception variable influences perceived usefulness. Fifth, video characteristics influence attitudes towards use. Sixth, the credibility variable influences attitudes toward use. Seventh, perceived usefulness variables influence attitudes toward use. Eighth, the perception of video characteristics influences the use of interest. Ninth, Attitudes toward use affect the interest to use.